The monotonicity of ratios involving arc tangent function with applications - Yang, Zhen-Hang; Tin, King-Fung; Gao, Qin (Open mathematics (Warsaw, Poland), 2019)
In this paper, we investigate the monotonicity of the functions on (0, ∞) for > 0, which not only gives relative errors of known bounds with quadratic for arctan , but also yields some new accurate bounds. Moreover, the known bounds are extended and a more accurate estimate for arctan is presented.